Basaloid Follicular Hamartoma: An Additional Criterion of Nevoid Basal Cell Carcinoma Syndrome. (15th January 2022) - Chikeka, Ijeuru; Chang, Li-Wei; Collins, Mary-Katherine; Pugliano, Melissa; Ho, Jonhan; House, Nancy; Kazlouskaya, Viktoryia
Abstract: Basaloid follicular hamartoma (BFH) is a rare, benign follicular neoplasm which typically presents as brown to skin-colored papules on the face, scalp, and trunk. Histologically, BFH consists of cords and strands of basaloid cells forming cystic structures with scant stroma and should be distinguished from infundibulocystic basal cell carcinoma to avoid overly aggressive treatment. Although BFH has been found to be associated with distinct syndromes, including alopecia, myasthenia gravis, and cystic fibrosis, there is often clinical, histopathologic, and genetic overlap with nevoid basal cell carcinoma syndrome (NBCCS). In this article, we describe a case of a 13-year-old patient with NBCCS who presented with multiple BFHs and propose that it its inclusion into the diagnostic criteria for NBCCS be considered.